Non-technical factors that influence the implementation of a knowledge management system in a parastatal organisation in South Africa - Majavu, Mluleki Justice (Department of Information Systems, 2022)
As the 4th Industrial Revolution (4IR) has influenced all sectors, and workers who accrued their experience over decades are reaching retirement age, it has become imperative in all sectors to access their knowledge, store it, and share it with new employees to avoid such knowledge being lost. Knowledge management aims to take advantage of the intangible assets that would otherwise be wasted: The knowledge developed and held by the organisations' employees, their accumulated experience, and task-specific knowledge acquired by employees. Hence, the importance of knowledge management (KM) practices in driving organisational growth and profitability is well established. However, there is a paucity of literature regarding the influence of non-technical attributes (employee attitude, organisational culture, and organisational politics) in driving the effective implementation of KM across public sector organisations. Hence, the present study addressed the gap in literature by exploring the non-technical attributes that influence the effective implementation of KM in South African parastatals. The present study was based on the assumption that non-technical attributes are as important as the technical attributes for ensuring effective KM implementation. The study was governed by the Ecological Theory of KM, which endorses that individuals, relationships, and learning communities play an important role, including their interaction with each other as well as internal and external factors that motivate them to share adequate, appropriate, and timely knowledge. This research contributes to the theoretical knowledge within the information systems (IS) community through developing models and theories in the extant literature that may account for the influence of organisational culture and politics in influencing the effective implementation of knowledge management systems (KMSs) in South African parastatal organisations. The evidence suggested that knowledge-sharing behaviour among employees is an important determinant for the effective implementation of KM. Hence, it was speculated that organisational culture and organisational politics might also influence KM implementation within South African parastatals by influencing the employee-related attributes. The ontological and epistemological stances that were considered for this study were objectivism and positivism, respectively. Such stances were adopted because it was contended that the realism related to KM implementation could be estimated through objective endpoints. A mixed-method approach was undertaken to obtain the relevant data from the participants. The subjective responses of the participants were obtained through closed-ended and open-ended questions. Since there are different non-technical factors that could influence the effective implementation of KM, it was hypothesised that a positive organisational culture or a positive employee attitude might not always ensure effective KM implementation. The hypotheses were grounded on the concept that a positive attitude by employees might become undermined by a dominant negative organisational culture, and destructive or over-bearing organisational politics. Under such circumstances, the positive attitude of employees would not be sufficient to influence effective KM implementation. The study showed that attitudes of people and a positive organisational culture significantly influenced an effective KM implementation. One of the novel findings in this study was that organisational politics did not significantly impact the implementation of KM practices (p > 0.05). However, the focus group interviews reflected that the parastatal organisation suffered from leadership challenges, which substantiated the lack of a relationship between politics and KM implementation. The major theory that emerged from this study was that knowledge sharing across a parastatal organisation is governed by the interaction of different knowledge-sharing theories. The novel finding that organisational politics might not significantly influence the effective implementation of a KMS could be explained from the theories of knowledge sharing, which mandate that trait theory and social engagement theory might interact in influencing knowledge sharing across employees of parastatal organisations. If organisational politics do not influence knowledge sharing, the altruistic attributes of an employee may still be sufficient to share tacit and explicit knowledge. Future studies should explore the direct interaction between the positive and negative attributes of people, organisational culture, and organisational politics in influencing an effective implementation of KM across a number of parastatal organisations.